Coding graphene metasurface modeling using MoM‐GEC method for dynamic diffusion and scattering control at Terahertz range. Issue 9 (18th June 2020) - Soltani, Imen; Soltani, Takoua; Aguili, Taoufik
Abstract: In this article, we present an electromagnetic study of electrically programmable graphene‐based metasurface with individual scattering control. Our investigation is based on the method of moments combined with the generalized equivalent circuit (MoM‐GEC) approach. We show that, tuning the unit cell's conductivity leads to change its input impedance and scattering matrix. So, each unit cell of the metasurface exhibits' a dynamic phase response that can be switched between 0° and −180° by controlling high transmission and total reflection states. Based on this feature, a 1‐bit coding metasurface consisting of discrete codes of "0" and "1" is used to synthesis 3D beams. Hence, tailorable anomalous reflection and diffusion are studied under normal incidence at a fixed frequency of 3.9 THz. This survey opens new opportunities in the domain of Terahertz beam engineering and security scanner applications.